Analyzing Customer Preferences towards Mobile Based Shopping (International Journal of Communication Systems and Network Technologies, 2018)
The main emphasis of this research paper is to study the customer preference towards various application of Mobile Commerce in current scenario. Mobile commerce refers to the ability to conduct wireless commerce transactions using mobile applications in mobile devices. It is a new concept and is emerging in a context of established norms, rules and standards. The adoption rate of m-commerce will increase based on the ease of its use and the increasing penetration of mobile and internet. Regarding the buying process for m-commerce, a variation on a more traditional commerce model is developed. However proper support from the Government and favourable regulations could further boost the growth of m-commerce. After online shopping, APP based shopping is growing  at a significant rate. People transact on APP based mobile device, where mobile is working as virtual store. After analysing the collected data, it is found that maximum persons agree that online shopping from mobile is more efficient and also they believe that they will intend to continue shopping using mobile phones. This paper analyzes the customer choice towards APP based mobile shopping especially in youth and females. Also, the survey identifies opportunities and challenges in APP based shopping.
Keywords: Mobile Commerce; APP; Customer